ATF7 mediates TNF-α–induced telomere shortening - Maekawa, Toshio (Nucleic Acids Res, 2018)
Telomeres maintain the integrity of chromosome ends and telomere length is an important marker of aging. The epidemiological studies suggested that many types of stress including psychosocial stress decrease telomere length. However, it remains unknown how various stresses induce telomere shortening. Here, we report that the stress-responsive transcription factor ATF7 mediates TNF-α–induced telomere shortening. ATF7 and telomerase, an enzyme that elongates telomeres, are localized on telomeres via interactions with the Ku complex. In response to TNF-α, which is induced by various stresses including psychological stress, ATF7 was phosphorylated by p38, leading to the release of ATF7 and telomerase from telomeres. Thus, a decrease of ATF7 and telomerase on telomeres in response to stress causes telomere shortening, as observed in ATF7-deficient mice. These findings give credence to the idea that various types of stress might shorten telomere.